Women’s Biography in Modern Ukrainian Women’s War Fiction: the Case of the Novel Because It Hurts by Yevhenia Senik - Snizhana Zhygun (Czytanie Literatury)
The article deals with the interaction of authentic women’s war experience and ideological requirements while shaping the female biographical narrative in modern Ukrainian fiction as exemplified by the novel Because It Hurts by Yevhenia Senik. The idea of strengthening the national identity with the topics forbidden in Soviet times is presented in the introductory part. The main part of the article shows how the author seeks to respond to both public expectations connected with strengthening the national identity and the need to understand the psychological crises caused by the war. The novel unveils women’s war experience, shaping the social frames of memories about it and influencing the public perception of current women soldiers. However, rather than follow the ideological tradition, Senik focuses on women’s agency and self-awareness.